PENGARUH KESADARAN PAJAK, KUALITAS PELAYANAN FISKUS, TINGKAT PEMAHAMAN PAJAK, TINFKAT PENDAPATAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (Studi Empiris Pada SAMSAT Kota Surakarta) - Safina Fatmawati; Suyatmin Waskito Adi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of tax awareness, tax service quality, level of tax understanding, income and tax levels on taxpayer compliance in paying motor vehicle taxes at SAMSAT Surakarta City. This research uses data analysis method using multiple linear regression analysis, descriptive analysis, classical assumption test, and hypothesis testing using SPSS version 25 program. Primary data obtained from questionnaires using incidental sampling technique from 100 respondents who are taxpayers who are paying motor vehicle tax in Indonesia. SAMSAT Surakarta City. The results of this study indicate that taxes and income levels affect taxpayer compliance. The quality of tax service, the level of understanding of taxes and taxes have no effect on taxpayer compliance.